Pension System in the Changing Society - Botos, József; Botos, Katalin (Public Finance Quarterly, 2020)
In the past three decades, several attempts in various directions have been initiated for reforming the pension system. The reforms are needed to ensure financial viability on the one hand, and to achieve greater justice, on the other hand. Parametric reforms are not enough. A paradigm shift is needed in the pension system! To that end, the insurance paradigm in the state pension system must be replaced with an investment paradigm, and, to be more specific, to the paradigm of investing into human capital. We don’t save for our older selves, we repay our predecessors what they invested in us. Our work pensions would be complemented by the second channel payable based on children or based on the voluntary pension fund. The latter should be chosen by those who do not or could not have children. If they do, eventually, have children, they can change to the children-based pension channel. The proposed reform would result in greater justice at all events. It would, however, be a viable step. It could have a significant role in strengthening family solidarity, encouraging having children and the mitigation of demographic problems.